2015
DOI: 10.1002/adom.201500115
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Luminescence Switching of an Organic Solid: Controllable On–Off Persistent Room Temperature Phosphorescence and Stimulated Multiple Fluorescence Conversion

Abstract: wileyonlinelibrary.com COMMUNICATIONreported mechanochromic luminescent materials contain a single luminophore with two fl uorescent states, and thus their fl uorescence can be switched between two colors or two different intensities. [ 5a , 6 ] However, examples exhibiting mechanochromic phosphorescence are rather rarely seen in literature, except for a few metal complexes showing mechanochromic phosphorescence with short lifetimes. [ 7 ] It is known that room temperature phosphorescent (RTP) emissions often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
73
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(74 citation statements)
references
References 48 publications
0
73
0
Order By: Relevance
“…[1][2][3] As opposed to loosely bonded electrons in organometallic materials,t he highly bonded nature of electrons in pure organic materials restricts their ability to decay through radiative relaxation pathways from triplet states. [6][7][8][9][10][11][12][13] These discoveries sparked several attempts to find ag eneral strategy to design more of such materials for various applications.Itwas found that to yield efficient RTP, several key factors have to be considered. [4] In addition, the triplet states are easily quenched by atmospheric oxygen molecules through triplet-triplet energy transfer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] As opposed to loosely bonded electrons in organometallic materials,t he highly bonded nature of electrons in pure organic materials restricts their ability to decay through radiative relaxation pathways from triplet states. [6][7][8][9][10][11][12][13] These discoveries sparked several attempts to find ag eneral strategy to design more of such materials for various applications.Itwas found that to yield efficient RTP, several key factors have to be considered. [4] In addition, the triplet states are easily quenched by atmospheric oxygen molecules through triplet-triplet energy transfer.…”
mentioning
confidence: 99%
“…Therefore,triplet states in organic materials are prone to nonradiative relaxations through thermal and collisional processes. [6][7][8][9][10][11][12][13] These discoveries sparked several attempts to find ag eneral strategy to design more of such materials for various applications.Itwas found that to yield efficient RTP, several key factors have to be considered. As such, intensely phosphorescent materials are largely known to exist in inert gases and at very low temperatures,w hich in turn limits their practical applications.…”
mentioning
confidence: 99%
“…[12] In the host-guest molecular materials, the highly rigid short conjugated matrix could suppress k q (RT) caused by endothermic triplet-triplet energy transfer from guest to host molecules and effectively protect triplet excited species from oxygen, contributing substantially to the appearance of persistent RTP. [56] However, for most heavy atom-free conjugated molecular crystals with persistent RTP, [9,[14][15][16]25,26,[46][47][48][49][50][51] the quantum yield of persistent RTP (Φ p (RT)) of conjugated molecular crystals with an RTP lifetime approaching to 1 s is often a few percent or less. [56] However, for most heavy atom-free conjugated molecular crystals with persistent RTP, [9,[14][15][16]25,26,[46][47][48][49][50][51] the quantum yield of persistent RTP (Φ p (RT)) of conjugated molecular crystals with an RTP lifetime approaching to 1 s is often a few percent or less.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reports of RTP from heavy metal-free aromatic molecules under ambient conditions have been scarce. [19] Therefore, these materials are potentially useful for a variety of applications, such as thermometers, [20] security, [13,15,[21][22][23][24] stimuli sensors, [25,26] optical recording, [27][28][29] and bioimaging, [28,30,31] which are independent of autofluorescence. [11][12][13][14][15][16][17] Because heavy atom-free molecules with T 1 with strong ππ* characteristics have very small k p , [18] RTP from such conjugated structures exhibits persistent emission characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation